Dari Layar ke Kepercayaan: Bagaimana Dukungan Selebriti dan Faktor Lingkungan Membentuk Loyalitas Pelanggan dalam Mobile Banking - Chaerunisa, Danya Rizki Chaerunisa; Pranata, Sudadi Pranata; Purnamasari, Dewi Laily Purnamasari (ICON Publisher, 2025)
This study investigates how mobile banking services influence customer loyalty, with a focus on the mediating role of celebrity endorsement and the moderating effect of environmental factors. Drawing on the Elaboration Likelihood Model (ELM), the study tests five hypotheses using a structural equation modeling (SEM-PLS) approach. The results show that mobile banking services significantly influence both customer loyalty and perceptions of celebrity endorsements. However, celebrity endorsements do not significantly affect customer loyalty, nor do they mediate the relationship between mobile banking services and loyalty. Additionally, environmental factors were found not to moderate the relationship, indicating that loyalty is shaped more by internal service quality than external conditions. The findings emphasize the dominant role of central cues—such as functionality, reliability, and convenience—in digital service experiences, suggesting that peripheral cues like celebrity endorsements are insufficient to foster loyalty in utilitarian services like banking. Practically, the study recommends that financial institutions invest more in service innovation and customer-centric mobile platforms than in celebrity-based promotions. Theoretically, the research expands the ELM framework by illustrating its limitations in high-involvement digital service contexts. Future studies are encouraged to explore alternative mediators and extend the model across different service industries and cultural settings.